Temporal trends in the treatment and outcomes of patients with acute coronary syndrome according to bleeding risk. (3rd October 2022) - Arow, Z; Gabarin, M; Landa, D; Giladi, E; Losin, I; Beeri, G; Omlechenko, A; Neuman, Y; Assali, A; Pereg, D
Abstract: Background: High bleeding risk is associated with adverse clinical outcomes in patients with ACS. We aimed to evaluate temporal trends in the treatment and outcomes of ACS patients according to bleeding risk. Methods: Included were ACS patients enrolled in the ACSIS survey. Bleeding risk was calculated using the CRUSADE score. Patients were divided into 3 groups according to enrolment period: early (2002–2004), mid (2006–2010) and recent (2012–2018). Each group was further divided into 3 sub-groups according to bleeding risk (low, intermediate and high). The primary endpoints were 30-day MACE and 1-year all-cause mortality. Results: Included were 13, 058 ACS patients. Patients at high bleeding risk were more frequently treated with guideline-based medications and coronary revascularization regardless of enrollment period. ACS patients at high bleeding risk had higher rates of 30-day MACE and 1-year all-cause mortality in all enrolment periods. Among patients enrolled in early period, 30-day MACE rates were 10.8%, 17.5% and 24.3% (p<0.001), Among patients enrolled in mid period, 30-day MACE rates were 7.7%, 13.4% and 23.5% (p<0.001), and for patients enrolled in recent period, 30-day MACE rates were 5.7%, 8.6% and 16.2%, (p<0.001) in low, moderate and high bleeding risk group, respectively. Furthermore, among patients enrolled in early period, 1-year all-cause mortality rates were 2%, 7.7% and 23.6% (p<0.001), Among patients enrolled in mid period, 1-year all-cause mortality rates were 1.5%, 7.2% and 22.1% (p<0.001), and for patients enrolled in recent period, 1-year all-cause mortality rates were 2.1%, 6% and 22.4%, (p<0.001) in low, moderate and high bleeding risk group, respectively. These differences remained significant following a multivariate analysis. Conclusions: Despite the improvement in the treatment of ACS patients in recent years, high bleeding risk remains a very strong predictor of adverse clinical outcomes. Funding Acknowledgement: Type of funding sources: None.